Microstructural Records of Earthquakes in the Lower Crust and Associated Fluid‐Driven Metamorphism in Plagioclase‐Rich Granulites. Issue 5 (30th May 2018) - Petley‐Ragan, Arianne; Dunkel, Kristina G.; Austrheim, Håkon; Ildefonse, Benoit; Jamtveit, Bjørn
Abstract: Coseismic damage associated with earthquakes in the lower continental crust is accompanied by postseismic annealing and fluid‐mediated metamorphism that influence the physical and chemical development of the continental crust on regional scales. A transition from brittle deformation to crystal‐plastic recrystallization is a recurring characteristic of rocks affected by lower crustal earthquakes and is observed in plagioclase adjacent to pseudotachylytes in granulite facies anorthosites from the Bergen Arcs, western Norway. The microstructural and petrological records of this transition were investigated using electron microscopy, electron microprobe analysis, and electron backscatter diffraction analysis. Microfractures associated with mechanical twins are abundant within plagioclase and contain fine‐grained aggregates that formed by fragmentation with minor shear deformation. The presence of feather features, which are described for the first time in feldspar, suggests that fractures propagate at near the shear wave velocity into the wall rock of earthquake slip planes. Grain size insensitive recrystallization took place within the time frame of pseudotachylyte formation, forming high‐angle grain boundaries required for shear zone initiation. Fluid infiltration synfracture to postfracture facilitated the epitactic replacement of plagioclase by alkali feldspar and the nucleation of clinozoisite, kyanite, and quartz. The grain size reduction and crystallization associated with the microfractures create rheologically weak areas that have the potential to localize strain within the plagioclase‐rich lower crust. Key Points: Plagioclase deforms by microfracturing, mechanical twinning, and feather feature formation without major shear component Recrystallization of microfractures occurred within the time frame of pseudotachylyte formation Microstructures produced by coseismic damage control the spatial distribution of eclogite facies minerals